USING ARTIFICIAL INTELLIGENCE IN DEVELOPING THE DIGITAL ECONOMY - Khasan Shirinboyevich Rashidov; Otabek Olimovich Muslimov (European Science Publishing, 2024)
This article explores the role of artificial intelligence (AI) in advancing the digital economy, with a focus on its potential applications and transformative impact. It examines how AI contributes to economic growth by optimizing business processes, improving decision-making, and fostering innovation. The study emphasizes the integration of AI technologies into various sectors of the economy and highlights the challenges and opportunities for countries like Uzbekistan in embracing AI for digital transformation.
Keywords: Artificial intelligence, digital economy, economic development, innovation, AI applications, Uzbekistan.